Integrating Cultural Insight into Ergonomic Design: Enhancing Material Handling for Disabled Individuals in Plastic Bottled Water Production - Yaikaew Silrak; Kanogkan Leerojanaprapa; Sirikorn Singto; Suratsawadi Thongrattana; Artitaya Boonjiam; Kittiwat Sirikasemsuk (Journal of Posthumanism, 2025)
This study explored how integrating cultural sensitivity into ergonomic design enhanced material handling for disabled workers in a plastic bottled water production facility. Initial resistance from workers—stemming from fears of job loss and the devaluation of human labor—highlighted the need for an inclusive design approach. Using the Rapid Entire Body Assessment (REBA), the study identified high-risk postures, particularly during the transition between the bottle printing and packaging processes. The researchers co-designed material handling equipment that maintained human involvement while reducing physical strain. After implementation, REBA scores decreased from 11 to 2 and from 11 to 5 at two key points. The required force for bottle handling was also reduced from 12.96 newtons to 3.6 newtons. The findings demonstrated that ergonomics, when informed by cultural understanding, not only improved physical safety but also supported worker dignity and acceptance of technological change. Integrating human control into the design process was crucial for worker acceptance, ensuring that technology was seen as a tool to enhance, rather than replace, their labor.
Keywords: Ergonomics and Human Factors